2009
DOI: 10.30843/nzpp.2009.62.4809
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sticker adjuvants for their effects on retention and rainfastening of fungicide sprays

Abstract: Sticker adjuvants enhance adhesion of pesticide sprays to plant surfaces and increase their resistance to rain This study evaluated the effect of two different sticker adjuvant types organosilicone/latex and terpene based polymers on the retention and rainfastness of a protectant fungicide tolyfluanid on Vicia faba (broad bean) and/or Brassica oleracea (cabbage) foliage On hardtowet cabbage the organosilicone/latex stickers provided better spray retention than the terpene polymers Increasing rates of the forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…The time between application and precipitation may also influence the efficiency of the plant protection product. Similar results were reported by other authors for the control of arthropod pests, diseases and weeds (DINARDO-MIRANDA et al, 2004;BRASVAULT et al, 2009;GASKIN and STEELE, 2009;PANNACCI et al, 2010;ANDERSEN et al, 2014). Most studies indicate that the lower the application time and the rainfall, the lower the deposition of the phytosanitary product.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The time between application and precipitation may also influence the efficiency of the plant protection product. Similar results were reported by other authors for the control of arthropod pests, diseases and weeds (DINARDO-MIRANDA et al, 2004;BRASVAULT et al, 2009;GASKIN and STEELE, 2009;PANNACCI et al, 2010;ANDERSEN et al, 2014). Most studies indicate that the lower the application time and the rainfall, the lower the deposition of the phytosanitary product.…”
Section: Resultssupporting
confidence: 86%
“…Several authors reported negative effects of rainfalls after spraying of pesticides (DINARDO-MIRANDA et al, 2004;BRÉVAULT et al, 2009, GASKIN andSTEELE, 2009;PANNACCI et al, 2010;ANDERSON et al, 2014;BORGES et al, 2015;DECARO et al, 2016). A study conducted by Gautam et al (2016) showed that artificial rainfalls reduced the efficiency of insecticides against the fly Drosophila suzukii Matsumura (Diptera: Drosophilidae).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, adjuvants such as surfactants and polymer coatings can increase the rainfastness significantly by sticking the substance or its components (e.g., microcapsules) to the foliage or by reducing surface tension (Thacker and Young 1999;Hunsche 2006;Green and Beestman 2007;Gaskin and Steele 2009;Anderson et al 2014;Mela et al 2015). Not all factors seem to affect foliar dissipation equally, and often their effect is species-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Retained residues (no rain) were generally highest with the superspreader type adjuvants and lowest with the pinene polymer type adjuvants, which were no different to captan alone ( Table 3). The pinene adjuvants are known to have less effect on improving spray retention compared to the superspreader/latex stickers (Gaskin & Steele 2009). Light rain had little effect on residues on leaf scars (Table 3) and spurs (data not presented).…”
Section: Resultsmentioning
confidence: 94%
“…Once dry, the efficiency of recovery of the dye in these sprays from rough surfaces may have been lower than for the slow-drying captan and pinene sprays. Dye recoveries (wash-offs) are normally undertaken immediately after spraying and before sprays have dried (Gaskin & Steele 2009), but it was not possible in this study to harvest spurs while wet because significant loss of spray volume could have occurred.…”
Section: Resultsmentioning
confidence: 99%